Pengukuran Kinerja Anggaran Berbasis Value For Money pada Badan Pengelolaan Keuangan Daerah Provinsi DKI Jakarta - Salsabila Fakhira; Zaenal Muttaqin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was motivated by indications of problems related to a significant increase in budget realization from 2021 to 2022 in three activities. This research aims to measure budget performance based on the concept of value for money in the Management Agency Regional Finance (BPKD) of DKI Jakarta Province, using Mahmudi's theory in 2019. The research method used is descriptive qualitative using primary and secondary data sources. Data collection techniques were carried out through in-depth interviews, observation, literature study and documentation. The determination of informants is adjusted to research needs which include the budget sector, treasury sector, program and finance sub-sections, as well as the coaching sector. To ensure the validity of the data, source triangulation and technical triangulation were used. The results of this research recommend the need for planning activities that are in accordance with priorities and budget allocation that is right on target, and in accordance with the achievement of indicators. This aims to improve budget performance so that it becomes more economical, efficient and effective.